FACTORS AFFECTING THE LEARNING MOTIVATION OF STUDENTS WORKING AND STUDYING AT VIETNAM WOMEN'S ACADEMY IN THE SOUTH - Phan Thị, Cẩm Giang (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2021)
The article illustrates the results of determinants of student’s learning motivation of 125 students working and studying system at the Vietnam Women’s Academy in the South. By qualitative and quantitative research methods, the research results show that the influencing factors include internal factors and external factors have a positive impact on the learning skills of students. Therefrom, a number of suggestions are proposed so that students can have better learning motivation.